Avaliação da postura corporal em mulheres com câncer de mama - Barbosa, Juliana de Assis Novais (2012)
The breast cancer treatment may cause some physical complications and functional, with incipient studies of changes in body posture of these women. Objective: Apply the RPB protocol (Rotina Postural Biofotogramétrica) to assess the posture of women undergoing breast cancer treatment, to identify postural changes compared with the position of women without breast cancer and determine the biomechanical behavior of the measured angles in the front and back plane. Methodology: A descriptive longitudinal study, performed in a reference hospital for cancer treatment in Vitória/ES Brazil, approved by the UFES Ethics Committee. The sample consisted of 78 women (cases and controls), 39 with breast cancer and 39 without a breast cancer diagnosis. Postural assessment was performed by biophotogrammetry before surgery (PRE), after removal of the drain (PO1) and three months after surgery (PO2). Factor multivariate analysis was used in order to cluster the measured angles and verify the biomechanical behavior. The correlation between postural angles measured with the variables: age, type of surgery and surgery side was examined. The program used for analysis was the SPSS 18.0 and significance level of 5%. Results: The quadrantectomy surgery was predominant (51.2%) and the left side was more affected (61.5%). The pelvis and trunk of quadrantectomy women showed greater alignment compared to mastectomy women in PO1 and PO2 moments respectively. Women who have had surgery in the left breast had higher shoulder and trunk bent to the ipsilateral surgery side. The women body posture with and without a breast cancer diagnosis was similar. Angles multivariate analysis was performed in both groups (78 women) and allowed the creation of four dimensions where the strength of association between some angles showed a predictable pattern of biomechanical behavior. Conclusion: Postural changes are primarily found in mastectomy women emphasizing the importance of early Physiotherapist intervention in order to minimize future musculoskeletal problems. In adition, studies are necessary to clarify the long-term postural changes and their impact on women's lives.